1999
DOI: 10.1677/joe.0.1630447
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of the marmoset gonadotrophin releasing hormone receptor: Ser(140) of the DRS motif is substituted by Phe

Abstract: In order to facilitate the understanding of gonadotrophinreleasing hormone (GnRH) agonist and antagonist action in the primate animal model, the marmoset GnRH receptor (GnRH-R) was cloned and characterised. It was shown to have 95% and 85% sequence identity with the human and rat GnRH-Rs, respectively, and, when transiently expressed in COS-7 cells, it exhibited high-affinity des-Gly 10 , ]-GnRH binding, with a K d value similar to those of both the rat and human forms, but with a greatly reduced B max value.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…EC: Extracellular loop, IC: Intracellular loop. Accession numbers in EMBL/Genbank: Cg-GnRH-R: (oyster) (AJ890150); Cg-GnRH-RII-S (AM904566); Cg-GnRH-RII-L (AM904565); Cg-GnRH-R-TF (AM904567); Cj-GnRH-RII: (marmoset) Callithrix jacchus (AF368286); Clg-GnRH-RI: (catfish) Clarias gariepinus (X97497); Dm-AKH-R: Drosophila melanogaster (AF077299); Gg-GnRH-RI: (chicken) Gallus gallus (AJ304414); Xl-GnRH-RI: Xenopus laevis (AF172330) and Cj-GnRH-RI is from (Byrne et al, 1999). Fig.…”
Section: Alternative Splicing Of the Cg-gnrh-r Precursor Mrnamentioning
confidence: 99%
“…EC: Extracellular loop, IC: Intracellular loop. Accession numbers in EMBL/Genbank: Cg-GnRH-R: (oyster) (AJ890150); Cg-GnRH-RII-S (AM904566); Cg-GnRH-RII-L (AM904565); Cg-GnRH-R-TF (AM904567); Cj-GnRH-RII: (marmoset) Callithrix jacchus (AF368286); Clg-GnRH-RI: (catfish) Clarias gariepinus (X97497); Dm-AKH-R: Drosophila melanogaster (AF077299); Gg-GnRH-RI: (chicken) Gallus gallus (AJ304414); Xl-GnRH-RI: Xenopus laevis (AF172330) and Cj-GnRH-RI is from (Byrne et al, 1999). Fig.…”
Section: Alternative Splicing Of the Cg-gnrh-r Precursor Mrnamentioning
confidence: 99%
“…The Tyr/Ser residue is believed to be a potential phosphorylation site, acting as a substrate for a G‐protein receptor kinase and thus is important for receptor desensitization and internalization (Arora et al, 1997; Millar et al, 2004). Byrne et al (1999) found that the GnRH‐R in male marmosets had 95% and 85% sequence identity with that in humans and rats, respectively. However, the highly conserved DRY motif in the GnRH‐R in marmoset is substituted with DRF, i.e., Ser is substituted with phenylalanine (Phe), instead of DRS as in all other mammals that have been studied so far.…”
Section: Testicular Developmentmentioning
confidence: 99%
“…In the present study, the lamprey GnRHR and three of the four mutants of lamprey GnRHR all induced a decrease in receptor expression except the mutant DRY 151 which induced an increase in receptor expression. Other studies on the DRS motif in mammalian type I GnRHRs revealed that Ser could be involved in ligand binding and receptor internalization events (Arora et al, 1997; Arora et al, 1995; Byrne et al, 1999). Substituting Ser with Tyr increased both the ligand binding affinity and internalization (Arora et al, 1995) but substituting with Ala had no effect (Arora et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the type II GnRH receptor mutants may not be capable of augmenting internationalization. In addition, Byrne et al (1999) suggested that the third amino acid position in DRY and the phosphorylation in the site are not essential for internalization. This would support the result of our study that the rate of internalization of the DRE 151 , DRS 151 and DRY 151 mutants was similar to that of wild-type because the c-terminal tail was more essential for internalization, although DRX 151 , point deletion of His 151 deletion in DRH, decreased the rate of internalization compared to other mutants and the wild-type receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation